What Do the Data Tell Us about Inflation Expectations? - Francesco D'Acunto; Ulrike M. Malmendier; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2022)
Inflation expectations are central to economics because they affect the effectiveness of fiscal and monetary policy as well as realized inflation. We survey the recent literature with a focus on the inflation expectations of households. We first review standard data sources and discuss their advantages and disadvantages. We then document that household inflation expectations are biased upwards, dispersed across individuals, and volatile in the time series. We also provide evidence of systematic differences by gender, income, education, and race. Turning to the underlying expectations formation process, we highlight the role of individuals' exposure to price signals in their daily lives, such as price changes in groceries, the role of lifetime experiences, and the role of cognition. We then discuss the literature that links inflation expectations to economic decisions at the individual level, including consumption-savings and financial decisions. We conclude with an outlook for future research.
Keywords: C90; D14; D84; E31; E52; E71; G11; 330; beliefs formation; heterogeneous agents; macroeconomics with micro data; inflation exposure; experience effects; financial sophistication